The Effectiveness of PCR in Diagnosis of Fungal Keratitis - G. I. Krichevskaya; L. A. Kovaleva; I. D. Zyurnyayeva; P. V. Makarov; A. E. Andryushin (Oftalʹmologiâ)
Fungi implicated in mycotic keratitis include different species. Conventional methods for the diagnosis of fungal keratitis include staining of corneal scarpings, culture medium (Sabouraud agar) for isolating fungi.Purpose. To evaluate the effectiveness of polymerase chain reaction (PCR) for the detection of fungal etiology in comparison with the conventional diagnostic methods in cases with suspected fungal corneal ulcer.Patients and methods. Seven patients with severe corneal ulcers with more than 3 weeks duration. Corneal scarpings and corneal buttons from seven patients who had undergone therapeutic keratoplasty were used for microbiological and PCR analysis. PCR diagnostic kits for the differential detection of Candida albicans DNA and total fungi DNA (DNA Fungi), which allows to identify most pathogenic fungi without determining their species were used. Microbiological methods: microscopy of gramstained smears, culture techniques, including selective for fungi agar Saburo with chloramphenicol.Results. PCR: Fragments of all corneas removed from keratoplasty (6 patients) revealed fungal-common DNA (Fungi DNA) and did not detect Candida albicans DNA, which correlated with sowing results on Saburo medium (mold fungi found in 5 of 6 corneas). Fungi DNA was also detected in the corneal scraps taken prior to surgery; however, growth of fungi during sowing on various nutrient media was not found.Conclusion. Corneal fungal ulcers are a serious disease, often leading to visual disability. The rapid determination of etiology and the correct choice of therapy determines the outcomes of the disease. The advantage of PCR over the culture method: the speed of obtaining results (4 hours instead of 3–7 days); high sensitivity, which allows detecting fungi not only in the tissue of the removed cornea, but also in scrapes from the cornea ulcer of patients who previously received antifungal therapy. The presence of commercial kits for differential detection of fungal-common DNA and DNA of Candida albicans extends the possibilities of PCR in the screening diagnosis of fungal keratitis and the selection of drugs before determining the type of pathogen.